The Effect of Exposure to Polystyrene Microplastics in Feed on the Growth of Tilapia (Oreochromis niloticus) - Bagus Dwi Hari Setyono; Baiq Triska Saomadia; Rangga Idris Affandi (Postgraduate, University of Mataram, 2024)
Indonesia is a country that is rich in natural resources and has various potentials that can be developed, especially in the field of aquaculture. Aquaculture activity that is often carried out by Indonesian people is the cultivation of tilapia (Oreochromis niloticus). Apart from that, Indonesia is known as the second largest contributor of plastic waste in the world after China. The scattered plastic waste will be degraded into microplastics which can then spread to tilapia farming locations. The aim of this research is to determine the effect of exposure to polystyrene microplastics given to tilapia feed on their growth. The research method used was a completely randomized design with 4 treatments and 3 replications with doses P1 = 0 mg/0.75 g feed (control), P2 = 0.01 mg/0.75 g feed, P3 = 0.1 mg/ 0.75 g feed, and P4 = 1 mg/0.75 g feed. The parameters tested were absolute weight growth, absolute length growth, spesific growth rate (SGR), feed conversion ratio (FCR) and water quality. The results obtained were that the effect of exposure to polystyrene microplastics in feed was significantly different on absolute weight growth, SGR, and FCR in tilapia (Oreochromis niloticus), but not significantly different on absolute length growth.